2021
DOI: 10.1039/d1cc01072g
|View full text |Cite
|
Sign up to set email alerts
|

3-Benzoylquinoxalinone as a photoaffinity labelling derivative with fluorogenic properties allowing reaction monitoring under “no-wash” conditions

Abstract: Described herein is a compact benzophenone-quinoxalinone photoaffintiy labelling hybrid system with caged fluorescence properties. Upon visible blue LED irradiation (λmax 450 nm), this photo-crosslinker is able to covalently capture proteins...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…For instance, Murale et al reported the synthesis and application of a BODIPY bearing a modified benzophenone motif for protein functionalization . Recent reports have also explored the use of photochemistry to produce radioactive mAbs for positron emission tomography (PET) imaging and photoactivatable fluorophores for protein labeling and live cell tracking. …”
Section: Introductionmentioning
confidence: 99%
“…For instance, Murale et al reported the synthesis and application of a BODIPY bearing a modified benzophenone motif for protein functionalization . Recent reports have also explored the use of photochemistry to produce radioactive mAbs for positron emission tomography (PET) imaging and photoactivatable fluorophores for protein labeling and live cell tracking. …”
Section: Introductionmentioning
confidence: 99%
“…We continue to investigate the speculation that multiple proteins tagged with arylchloro-pcBD may be involved in cellular GSH transport mechanisms. Sabot et al designed similar benzophenone-mimetic fluorogenic probes (Figure A) . They presented 3-benzoyl­quinoxalinone probes that labeled proteins via the Norrish Type I diradical generation mechanism using visible blue LED irradiation instead of UV excitation limited to in vitro conditions.…”
Section: Multifunctional Photo-cross-linkermentioning
confidence: 99%
“…Sabot et al designed similar benzophenone-mimetic fluorogenic probes (Figure 5A). 46 They presented 3-benzoylquinoxalinone probes that labeled proteins via the Norrish Type I diradical generation mechanism using visible blue LED irradiation instead of UV excitation limited to in vitro conditions.…”
Section: Fluorogenic Photo-cross-linkers For Bioimagingmentioning
confidence: 99%
“…Fluorogenic 3‐benzoylquinoxalin‐2(1 H )‐ones 169 were recently employed by our team as photoreactive moieties in the design of photoaffinity probes (Scheme 24). [67] Photoaffinity labelling generally relies on the use of photoreactive functions including benzophenones, diazirines or phenylazides, which generate highly reactive species able to covalently bind protein target in response to light activation. As previously mentioned, (c.f.…”
Section: Applicationsmentioning
confidence: 99%